Graphene : an introduction to the fundamentals and industrial applications - Sharon, Madhuri; Sharon, Maheshwar (Hoboken, New Jersey : Wiley, 2015)
"Often described as a 'miracle material', graphene's potential applications are extraordinary, ranging from nanoscale 'green' technologies, to sensors and future conductive coatings. This book covers the topic of 'graphene' -- the history, fundamental properties, methods of production and applications of this exciting new material. The style of the book is both scientific and technical -- it is accessible to an audience that has a general, undergraduate-level background in the sciences or engineering, and is aimed at industries considering graphene applications. As the graphene topic is a broad-reaching and rapidly moving field of research, the aim of this book is therefore to provide information about graphene and its current and future applications that are immediately implementable, relevant and concise. After reading this book, the reader will have sufficient knowledge and background to move forward independently into graphene R&D and to apply the knowledge therein. Although the book will be self-contained, each chapter has copious references to enable further reading, research and exploration of the chapter topics"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Graphene -- Industrial applications; Graphene; TECHNOLOGY & ENGINEERING / Material Science; Electronic books; Electronic books